2020
DOI: 10.1111/pace.14022
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term follow‐up of the two‐incision implantation technique for the subcutaneous implantable cardioverter‐defibrillator

Abstract: Introduction: The two-incision implantation technique of the subcutaneous implantable cardioverter-defibrillator (S-ICD) was introduced as an alternative to the standard three-incision approach by omitting the superior parasternal incision. Thereby, complications may be prevented. Short-term follow-up demonstrated the safety and efficacy of the two-incision technique. However, long-term results are lacking. Methods: This retrospective study included patients implanted between February 2009 and June 2020. Patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 14 publications
3
17
0
Order By: Relevance
“…This hypothesis did not align with our findings, which revealed no statistically significant difference between the two groups in lead dislocation, inappropriate shocks, defibrillation test failure, and first shock efficacy. Our findings match the results of previous studies by El Chami et al., Stuijt et al., and Brouwer et al 17,18,21 . Brouwer et al 21 .…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This hypothesis did not align with our findings, which revealed no statistically significant difference between the two groups in lead dislocation, inappropriate shocks, defibrillation test failure, and first shock efficacy. Our findings match the results of previous studies by El Chami et al., Stuijt et al., and Brouwer et al 17,18,21 . Brouwer et al 21 .…”
Section: Discussionsupporting
confidence: 93%
“…We couldn't meta-analyze hematoma as this outcome was reported only in two studies. 18,21 In Brouwer et al, 21 no hematomas occurred in 2IT or 3IT groups, making the estimation of pooled RR inappropriate.…”
Section: Hematomamentioning
confidence: 99%
“…That selection factor became dominant, which brought Polish data closer to European reports [8]. Novel operational techniques reported in the literature, such as regional anesthesia, 2-incision technique and intramuscular pocket [9][10][11][12], have been introduced in Polish centers ever since. Those techniques have become dominant, and our results suggest that general anesthesia may be soon replaced by local and regional anesthetic techniques.…”
Section: Resultsmentioning
confidence: 99%
“…Although operators have evolved with regard to surgical techniques at our center over time, the number of patients with two and three‐incision techniques was similar. In a study by Stujit et al, 5‐year follow‐up of the S‐ICD cohort showed similar complication rates and effectiveness of the two‐incision technique compared with the three‐incision technique 27 …”
Section: Discussionmentioning
confidence: 86%